Analysis of nursing dissertations and thesis on ostomy wounds, Brazil, 1979-2005 - Adriana Karla Silva Correia; Thereza Maria Magalhães Moreira; Maria Euridéa de Castro; Consuelo Helena Aires de Freitas Lopes; Maria Salete Bessa Jorge (Rev Rene)
The study of the development of knowledge on ostomy represents a great contribution to Health. This study aimed at investigating the material about the subject produced in the Brazilian nursing academy from 1979 to 2005. A documental research was performed to collect abstracts from dissertations and thesis at the Center for Study and Research in Nursing (CEPEN) from 1979 to 2005. Results showed a total of 22 papers, among which 19 dissertations, two doctorate thesis and one thesis for the purpose of attaining the rank of associate professorship. As shown by the study, papers were concentrated, geographically speaking, predominantly in the South and Southeastern regions of the country. Key subjects underlying all the 22 papers were primarily professional approach and patient’s adaptation to ostomy. As observed in the investigation, studies are required to encourage a holistic understanding of the ostomized person, with approaches that address their family and social relationship. Moreover, a biopsychosocial approach is also required.